Effects of satellite transmitters on captive and wild mallards - Dylan C. Kesler; Andrew H. Raedeke; Jennifer R. Foggia; William S. Beatty; Elisabeth B. Webb; Dale D. Humburg; Luke W. Naylor (Wildlife Society Bulletin)
ABSTRACT Satellite telemetry has become a leading method for studying large‐scale movements and survival in birds, yet few have addressed potential effects of the larger and heavier tracking equipment on study subjects. We simultaneously evaluated effects of satellite telemetry equipment on captive and wild mallards (Anas platyrhynchos) to assess impacts on behavior, body mass, and movement. We randomly assigned 55 captive ducks to one of 3 treatment groups, including a standard body harness group, a modified harness group, and a control group. Ducks in the control group were not fitted with equipment, whereas individuals in the other 2 groups were fitted with dummy transmitters attached with a Teflon ribbon harness or with a similar harness constructed of nylon cord. At the conclusion of the 14‐week captive study, mean body mass of birds in the control group was 40–105 g (95% CI) greater than birds with standard harnesses, and 28–99 g (95% CI) greater than birds with modified harnesses. Further, results of focal behavior observations indicated ducks with transmitters were less likely to be in water than control birds. We also tested whether movements of wild birds marked with a similar Teflon harness satellite transmitter aligned with population movements reported by on‐the‐ground observers who indexed local abundances of mid‐continent mallards throughout the non‐breeding period. Results indicated birds marked with satellite transmitters moved concurrently with the larger unmarked population. Our results have broad implications for field research and suggest that investigators should consider potential for physiological and behavioral effects brought about by tracking equipment. Nonetheless, results from wild ducks indicate satellite telemetry has the potential to provide useful movement data. © 2014 The Wildlife Society.